William Bradford papers - Bradford, William, 1663-1752.
Holograph document (1710 February 8) concerning an act of the New York General Assembly pertaining to the construction and repair of public buildings along with a facsimile and typewritten transcript of the document, facsimile of letter (New York; 1726 June 28) also relating to acts of the assembly, and a facsimile of a lithograph of Bradford's tombstone.
In part, facsimiles and typewritten transcript.
Government and commercial printer from New York, N.Y. Inscription on tombstone gives 1660 as his date of birth.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: New York (State). -- General Assembly; Public buildings -- New York (State).; Printers